Endothelial dysfunction, platelet activation, thrombogenesis and fibrinolysis in patients with hypertensive crisis - van den Born, Bert-Jan H; Löwenberg, Ester C; van der Hoeven, Niels V; de Laat, Bas; Meijers, Joost C M; Levi, Marcel; van Montfrans, Gert A (Journal of hypertension, 2011)
Hypertensive crisis is an extreme phenotype of hypertension and hypertension-related thrombotic complications. This is most evident in patients with hypertensive crisis having advanced retinopathy and thrombotic microangiopathy (TMA). We examined whether hypertensive crisis complicated by advanced retinopathy is associated with endothelial dysfunction, platelet activation, thrombin generation and decreased fibrinolytic activity. In addition, we tested the association between these procoagulant changes and the development of TMA and end-organ dysfunction. Several key mediators of coagulation were assessed in 40 patients with hypertensive crisis with and without retinopathy and compared with 20 age, sex and ethnicity-matched normotensive controls. In patients with hypertensive crisis, associations with markers of TMA and renal dysfunction were assessed by regression analysis. Soluble P-selectin levels were higher in patients with hypertensive crisis compared with controls regardless of the presence or absence of retinopathy (P<0.01). Levels of von Willebrand factor (VWF), VWF propeptide, prothrombin fragment 1+2 (F1+2) and plasmin-antiplasmin (PAP) complexes were significantly higher in hypertensive crisis with retinopathy compared with normotensive controls (P-values<0.01), whereas in patients without retinopathy only VWF propeptide was higher (P=0.04). VWF, VWF propeptide, soluble tissue factor, F1+2 and PAP were positively associated with markers of TMA and renal dysfunction (P≤0.05). Hypertensive crisis with retinopathy confers a prothrombotic state characterized by endothelial dysfunction, platelet activation and increased thrombin generation, whereas fibrinolytic activity is enhanced. The observed changes in prothrombotic and antithrombotic pathways may contribute to the increased risk of ischaemic and haemorrhagic complications in this extreme hypertension phenotype.